The Impact of Product Quality, Corporate Image, and Service Quality on Property Product Purchase Decisions at HZ Property Company - Rahmadani; Endang Sulistya Rini; Syahyunan (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of product quality, corporate image, and service quality on property product purchasing decisions at the HZ Property company in Medan. The background of this study is the low purchase conversion even though the company has developed projects in strategic locations. This study uses a quantitative approach with a survey method through a questionnaire to 85 respondents who are HZ Property consumers, which is determined using the Slovin formula. The independent variables in this study are product quality, corporate image, and service quality, while the dependent variable is the purchase decision. The data analysis technique used is multiple linear regression with the help of SPSS. The results of the study show that the three independent variables have a significant effect on purchasing decisions, both partially and simultaneously. Consistent product quality, positive corporate image, and responsive service have been shown to increase consumer trust and buying interest. These findings provide theoretical contributions in the development of property consumer behavior studies, as well as practical benefits for HZ Property in formulating customer preference-based marketing strategies. This study also fills the literature gap by highlighting the simultaneous influence of the three variables on the local property sector. With an integrative approach, the results of this study are expected to be a strategic reference in improving property sales performance amidst increasingly competitive market competition.